Korelasi Pengetahuan Tentang Kesehatan Reproduksi Terhadap Perilaku Pencegahan Kehamilan Tidak Diinginkan di Kota Denpasar - Putu Noviana Sagitarini; Ni Komang Tri Agustini (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Background: Unwanted Pregnancy is a condition where the couple does not want the birth of a pregnancy. Unwanted pregnancy is a major challenge to the reproductive health of young adults in developing countries. Purpose: The purpose of the study was to measure the relationship between the level of knowledge and adolescent behavior in preventing unwanted pregnancy in nursing students. Methods: This study uses cross sectional correlative analytic to determine knowledge about reproductive health on the behavior of preventing unwanted pregnancy. The research sample was 207 nursing students. Data obtained through questionnaires and analyzed using univariate and bivariate analysis with chi-square. Results: Univariate results showed that 152 respondents (73.4%) had good knowledge, and 155 respondents (74.9%) showed supportive pregnancy prevention behaviors. The results of bivariate analysis showed that there was a relationship between knowledge level and pregnancy prevention behavior (x2=4.26, p <0.05). Conclusion: Most of the students have a good level of knowledge and have supportive pregnancy prevention behaviors